Projected climatic changes lead to biome changes in areas of previously constant biome - Brian Huntley; Judy R. M. Allen; Matthew Forrest; Thomas Hickler; Ralf Ohlemüller; Joy S. Singarayer; Paul J. Valdes (Journal of Biogeography, 2021)
Aim Recent studies in southern Africa identified past biome stability as an important predictor of biodiversity. We aimed to assess the extent to which past biome stability predicts present global biodiversity patterns, and the extent to which projected climatic changes may lead to eventual biome changes in areas with constant past biome. Location Global. Taxon Spermatophyta; terrestrial vertebrates. Methods Biome constancy was assessed and mapped using results from 89 dynamic global vegetation model simulations, driven by outputs of palaeoclimate experiments spanning the past 140 ka. We tested the hypothesis that terrestrial vertebrate diversity is predicted by biome constancy. We also simulated potential future vegetation, and hence potential future biome patterns, and quantified and mapped the extent of projected eventual future biome change in areas of past constant biome. Results Approximately 11% of global ice‐free land had a constant biome since 140 ka. Apart from areas of constant Desert, many areas with constant biome support high species diversity. All terrestrial vertebrate groups show a strong positive relationship between biome constancy and vertebrate diversity in areas of greater diversity, but no relationship in less diverse areas. Climatic change projected by 2100 commits 46%–66% of global ice‐free land, and 34%–52% of areas of past constant biome (excluding areas of constant Desert) to eventual biome change. Main conclusions Past biome stability strongly predicts vertebrate diversity in areas of higher diversity. Future climatic changes will lead to biome changes in many areas of past constant biome, with profound implications for biodiversity conservation. Some projected biome changes will result in substantial reductions in biospheric carbon sequestration and other ecosystem services.